Developmental trajectories of cerebrovascular reactivity in healthy children and young adults assessed with magnetic resonance imaging. (17th March 2016) - Leung, Jackie; Kosinski, Przemyslaw D.; Croal, Paula L.; Kassner, Andrea
Abstract : Key points: Cerebrovascular reactivity (CVR) reflects the vasodilatory reserve of cerebral resistance vessels. Normal development in children is associated with significant changes in blood pressure, cerebral blood flow (CBF) and cerebral oxygen metabolism. Therefore, it stands to reason that CVR will also undergo changes during this period. The study acquired magnetic resonance imaging measures of CVR and CBF in healthy children and young adults to trace their changes with age. We found that CVR changes in two phases, increasing with age until the mid‐teens, followed by a decrease. Baseline CBF declined steadily with age. We conclude that CVR varies with age during childhood, which prompts future CVR studies involving children to take into account the effect of development. Abstract: Cerebrovascular reactivity (CVR) reflects the vasculature's ability to accommodate changes in blood flow demand thereby serving as a critical imaging tool for mapping vascular reserve. Normal development is associated with extensive physiological changes in blood pressure, cerebral blood flow and cerebral metabolic rate of oxygen, all of which can affect CVR. Moreover, the evolution of these physiological parameters is most prominent during childhood. Therefore, the aim of this study was to use non‐invasive magnetic resonance imaging (MRI) to characterize the developmental trajectories of CVR in healthy children and young adults, and relate them to changes in cerebral blood flow (CBF). Thirty‐four healthy subjects (17 males, 17 females; age 9–30 years) underwent CVR assessment using blood oxygen level‐dependent MRI in combination with a computer controlled CO2 stimulus. In addition, baseline CBF was measured with a pulsed arterial spin labelling sequence. CVR exhibited a gradual increase with age in both grey and white matter up to 14.7 years. After this break point, a negative correlation with age was detected. Baseline CBF maintained a consistent negative linear correlation across the entire age range. The significant age‐dependent changes in CVR and CBF demonstrate the evolution of cerebral haemodynamics in children and should be taken into consideration. The shift in developmental trajectory of CVR from increasing to decreasing suggests that physiological factors beyond baseline CBF also influence CVR. Key points: Cerebrovascular reactivity (CVR) reflects the vasodilatory reserve of cerebral resistance vessels. Normal development in children is associated with significant changes in blood pressure, cerebral blood flow (CBF) and cerebral oxygen metabolism. Therefore, it stands to reason that CVR will also undergo changes during this period. The study acquired magnetic resonance imaging measures of CVR and CBF in healthy children and young adults to trace their changes with age. We found that CVR changes in two phases, increasing with age until the mid‐teens, followed by a decrease. Baseline CBF declined steadily with age. We conclude that CVR varies with age during childhood, which prompts future CVR studies involving children to take into account the effect of development.